Asymmetry Price Transmission in Market Rice in Indonesia - Novianti, Tanti; Mashito, Mulia Ary; Muryani, Muryani (Jurnal Ilmu Ekonomi Terapan, 2020)
Rice price disparity at the farmer and consumer level is large. This study analyzes the movement and transmission of rice pricer at the producer and consumer level between regions in Indonesia. The data used in this study is data on rice and beef prices at the producer and consumer level from 2010 to 2017. The method used in the analysis is the Error Correction Model (ECM). The movement of rice between regions in Indonesia fluctuated throughout the period 2010- 2017. The price of rice at the producer level is more volatile than the price of rice at the consumer level. Transmission of rice prices at the consumer level to prices at the producer level occurs asymmetrically, both in the short term and in the long run. In producer- consumer relations, the transmission of rice prices at the producer level to prices at the consumer level occurs asymmetrically in the short term, but symmetrically in the long run.